A Comparative Analysis of Party Coalition Systems in Indonesia’s Presidential Government and Australia’s Parliamentary Tradition - Rahmadani Rahmadani (Journal Evidence Of Law, 2025)
This article examines the comparative dynamics of party coalitions within Indonesia’s presidential system and Australia’s parliamentary system, focusing on how coalition structures shape legislative functions and the quality of democratic governance. Using a qualitative comparative approach and descriptive-analytical methods, the study finds that in Indonesia’s multiparty presidential system, coalition formation tends to be pragmatic in the pursuit of stability, yet it often weakens parliamentary oversight and undermines substantive public representation. In contrast, Australia’s parliamentary coalitions are more stable and ideologically aligned, allowing legislative functions to remain deliberative and accountable despite the integration of executive and legislative powers. The findings demonstrate that institutional design and political culture significantly shape coalition outcomes; Indonesia’s coalitions tend to foster legislative capture due to weak opposition, whereas Australia’s coalition arrangements coexist with strong accountability mechanisms. The article recommends reforms to strengthen Indonesia’s party system and coalition practices, including reinforcing parliamentary opposition and promoting policy-based coalition platforms, so that political stability does not come at the expense of oversight and democratic representation.